Hodnocení účinnosti systémového podání tranexamové kyseliny (Exacylu) u náhrad kyčelního a kolenního kloubu – prospektivní kohortová studie - Hillová Mannová, Jitka; Kubát, Pavel; Pospíchal, Martin; Longin, Pavel (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2019)
PURPOSE OF THE STUDY To evaluate the efficacy of the systemic administration of two doses of tranexamic acid (TXA) in total knee (TKA) and hip arthroplasty (THA). MATERIAL AND METHODS The study evaluated a total of 295 patients who underwent total knee and hip arthroplasty for osteoarthritis, prospectively followed up were the patients who had been administered the tranexamic acid (TXA), and this group was subsequently compared against the cohort - control group. Our evaluation was focused on perioperative and postoperative period. The amount of blood loss was monitored during the surgery as well as postoperatively. Moreover, the frequency and the volume of administered allogeneic blood transfusions and in TKA also autotransfusion requirement were observed. The patients postoperative hemoglobin levels were compared in both the groups when the patients were in the ICU and the frequency of all postoperative complications was monitored. The statistical analysis was carried out separately for hip and knee replacement. RESULTS Our study confirmed that the systemic application of tranexamic acid in two 10-15 mg/kg doses in knee arthroplasty resulted in a statistically significant reduction of perioperative and postoperative blood loss, lower frequency of administration of allogeneic blood transfusion, but also in lower frequency in the administration of any transfusion, including autotransfusion. In patients who underwent total hip arthroplasty, the administration of TXA led to a statistically significant reduction of postoperative bleeding. The patients with total knee as well as hip arthroplasty, who had been administered TXA, showed significantly higher haemoglobin levels when transferred from the ICU. No significant difference was found in deep vein thrombosis, pulmonary embolism or other postoperative complications among the study groups. DISCUSSION There is no homogeneity in the already published studies proving the efficacy of TXA in TKA and THA, they differ considerably as to the method of administration of the tranexamic acid. The differences concern the systemic and local application, dosage and time of administration. In some studies, TXA was administered in a single dose only, whereas in other studies it was administered repeatedly, in the form of a bolus or continuously. In our study we confirmed the efficacy of systemic administration of tranexamic acid in two repeated bolus doses of 10-15 mg/kg, namely before the commencement of the surgery and at the end of the surgery. CONCLUSIONS The administration of tranexamic acid in two IV doses of 10-15 mg/kg to patients with total knee and hip arthroplasty has proven to be efficient. A higher efficacy of TXA was reported in TKA and due to routine administration of TXA the postoperative autotransfusion system (ORTHO P.A.S.) ceased to be used in knee replacement surgery. Key words:total hip arthroplasty, total knee arthroplasty, tranexamic acid, blood loss, allogeneic transfusion, autotransfusion, postoperative complications.
Keywords: Blood Loss, Surgical; antifibrinolytika; krvácení při operaci; Tranexamic Acid; Antifibrinolytic Agents; náhrada kyčelního kloubu; lidé; Arthroplasty, Replacement, Hip; kyselina tranexamová; Arthroplasty, Replacement, Knee; prospektivní studie; Prospective Studies; totální endoprotéza kolene; Humans